Over-the-counter hearing aids: implementations and opportunities - Chung, King; Zeng, Fan-Gang (Frontiers in Audiology and Otology, 2024)
After decades of effort by shareholders, including government agencies, patient advocacy groups, and professional organizations, the U.S. Food and Drug Administration (FDA) established a new medical device category for over-the-counter (OTC) hearing aids on October 17, 2022. This FDA regulation allows adults aged 18 years or older with perceived mild-to-moderate hearing loss to purchase OTC hearing aids without a prescription or even a hearing test. The goal is to increase hearing aid accessibility, potentially leading to improved hearing and a better quality of life. In our analysis of the FDA Establishment Registration & Device Listing database, we found that the current OTC hearing aid market is still dominated by traditional hearing aid manufacturers, with limited disruptor from major consumer electronics and startup companies. Our technological analyses showed that the relatively high-level output specification without gain limitation allows sufficient amplification even for people with severe-to-profound hearing loss. Additionally, borrowing from the cochlear implant mapping strategy, we propose novel amplification algorithms for fitting OTC hearing aids without an audiogram. We argue that smartphones and true-wireless-stereo earbuds can functionally serve as OTC hearing aids, further increasing accessibility and affordability while reducing the stigma associated with hearing aids, especially in low- and mid-income countries. By treating more people at a younger age with less hearing loss than traditional prescription hearing aids, OTC hearing aids can potentially have a significant impact beyond hearing care, such as delaying or preventing cognitive decline in the elderly.